Hermeneutika Dialogis sebagai Basis Filosofis dalam Fiksyen dan Sejarah, Suatu Dialog Karya Umar Junus - Suharmono (Sasdaya: Gadjah Mada Journal of Humanities, 2023)
This study aims to explain dialogical hermeneutics, one of the scientific paradigms that can bridge the confusion of thinking in explaining the relationship between literature and reality/history. The material object used is Fiction and History of Dialogue, while the formal object is the dialogical hermeneutic paradigm in the book. The purpose of this study is to describe the basic assumptions; model; and the concepts that make up dialogic hermeneutics. The theoretical framework and method used as the basis for the analysis are Thomas Khun's thoughts related to paradigms. The results of the research show that Fiction and Dialogue History books criticize in discussing fiction which is dominated by mimetic and semiotic concepts as well as history which is seen as something that is often contrasted with fiction. Junus offers an alternative idea in the form of dialogue (hermeneutics) as a new way of looking at the relationship between fiction and history/reality. Junus uses an analogy model to see the relationship between fiction and history/reality. The concepts put forward include the Concept of Definition of Fiction; The Nature of Reality in Stories; Fiction and Heurmenetics; Fiction Shapes Reality; Perspective of Fiction and Reality of Writers and Readers; and Fiction and History.